(untitled) (Studia Prawnicze / The Legal Studies, 1981)
Democracy, to which only socialism for the first time gave the real meaning, is one of the fundamental principles of building developed socialist society. Experience of the German Democratic Republic prove that participation of the working masses in solving tasks and making state decisions on all the levels constitutes moving forces of social development, and that the fundamental task of the state is to activise such creative participation according to the principle that all the power derives from the people and serves its interests. Together with the developement of socialism humanitarian character of socialist democracy is more distinct and it is particularity reflected in deepening the possibilities of national economy and in shaping socialist social relations. Socialist state, in its aims and tasks, in its forms and methods as well as in its personal composition, is determined by the leading role of the marxist- leninist party. And as far as development of democracy in the DDR is concerned, it is characterized by close cooperation of the Socialist Unity Party of Germany with the remaining political parties. In the DDR great attention is paid to the development of socialist democra- cy in the sphere of material production, and especially to the increase of im- portance of the working collectives and trade unions. Representation, i.e. working assemblies in which all political parties ancl mass organizations are represented by the deputees elected in democratic elect- ions, plays fundamental role in developing socialist democracy in the DDR. The forms of activity of utmost importance are sessions, during which plans of so- cio-economic development, budgets, long-term (perspective) plans, etc. are adopt- ed. Projects of resolutions of special importance from social point of view are publicly discussed. Socialist democracy includs also dense network of social organs (e.g. commis- sions), so that active cooperation of the citizens in all the domains of state management and planification is guaranteed. Together with the development of socialist democracy the range of rights and freedoms of the citizens widens, as well as the possibilities of genuine making use of them by the working people. In this situation attentive and non-bu- reaucratic way of settling affairs of the citizens by state organs is of utmost importance.